THE POSITION OF THE CONSUMER DISPUTE SETTLEMENT BODY IN THE EFFORT TO SUBMIT A CONSUMER DISPUTE OBJECTION - Wibowo, Veronica Cynthia; Subagyono, Bambang Sugeng Ariadi; Chumaida, Zahry Vandawati (UNISSULA, 2023)
The purpose of this study is to analyse PERMA No. 1 of 2006 which is a guideline for the District Court as well as consumers and business actors regarding the procedure for filing objections to decisions of the Consumer Dispute Resolution Agency (BPSK) which had not previously been regulated in the UUPK Law. One of the things that is regulated in PERMA No. 1 of 2006 through Article 3 paragraph (3) is that the Consumer Dispute Resolution Body is not a party to the filing of objections to consumer disputes. Article 3 paragraph (3) of PERMA No. 1 Of 2006 contains new norms that were not previously regulated by the UUPK. This research discusses the ratio legis of BPSK not being a party in the objection of consumer disputes and how the legal consequences of BPSK as a Respondent in the objection of consumer disputes. This research is a doctrinal legal research that uses statute approach and conceptual approach. The results of the analysis of the writing of Article 3 paragraph (3) of PERMA No. 1 Of 2006 as a form of affirmation that BPSK is not a party, but an institution that has the duty and authority to handle and resolve consumer disputes. The existence of Article 3 paragraph (3) of PERMA 1/2006 gives legal consequences that if BPSK is included as a party to the objection, the District Court will give a decision that the lawsuit cannot be accepted. Although there are differences in the regulations in UUPK and PERMA 1/2006, with the existence of the AAPS Law, if there are problems related to arbitration at BPSK, the legal rules used are special rules, namely UUPK and its derivative rules including PERMA 1/2006.